On the Detectability of Large-Scale Flows by Asteroseismology - Roth, Markus; Herzberg, Wiebke (Frontiers in Astronomy and Space Sciences, 2020)
Large-scale convective motions are an integral part of stellar interior dynamics and might play a relevant role in stellar dynamo processes. However, they are difficult to detect or characterize. Stellar oscillations are affected by convective flows due to advection. For the Sun, forward calculations of the advective effect of flows on oscillation modes have already been conducted, but the effect has not yet been examined for other types of stars. Suitable candidates are subgiant or red giant stars, since they possess extensive outer convection zones, which likely feature large-scale flow cells with strong flow velocities. We investigate the effects of large-scale flows on oscillation modes of subgiant stars by means of forward calculations based on an exemplary subgiant stellar model. We focus in particular on non-axisymmetric cell formations, also referred to as giant cells. The effects are described in the non-rotating and the rotating case. By solving the forward problem, we evaluate, if large-scale flow cells lead to signatures in asteroseismic data that are suitable for the detection of such flows. The influence of flows is calculated by employing perturbation theory as proposed by Lavely & Ritzwoller (1992), where the flow is treated as a perturbation of a 1D equilibrium stellar model. The presence of a flow leads to a coupling of the modes, which results in frequency shifts and a mixing of the mode eigenfunctions. For a non-rotating star, non-axisymmetric flows lead to degeneracies between coupling modes, which cause an asymmetry in the frequency shifts of modes of opposite azimuthal order. If rotation is included, the degeneracy is lifted in first order, but residual degenerate coupling and third order effects can still lead to asymmetries, depending on whether the modes are of p- or of g-type. For rotating stars, the mode mixing induced by non-axisymmetric flows causes the observational signal of a perturbed mode to be multiperiodic, which becomes visible in the power spectrum. An expression for the amplitudes of the signal’s different components is derived.